Toxic effects and primary source of the aged micro-sized artificial turf fragments and rubber particles: Comparative studies on laboratory photoaging and actual field sampling. (December 2022) - Xie, Linyang; Zhu, Kecheng; Jiang, Wenjun; Lu, Haodong; Yang, Huiqiang; Deng, Yongxi; Jiang, Yuanren; Jia, Hanzhong
Graphical abstract: Highlights: MATF and MRP enriched substantial heavy metals and PAHs from the environment. MATF and MRP from actual artificial turf had significantly higher cytotoxicity. EPFRs and ROS had limited contributions to the cytotoxicity of aged MATF and MRP. Heavy metals and PAHs played important roles in the toxicity of MATF and MRP. Abstract: Numerous micro-sized artificial turf fragments (MATF) and rubber particles (MRP) are generated and accumulated during the use of the artificial playing field. However, attention has rarely been paid to the potential toxic effects of MATF and MRP on sportsmen. In this study, the active components and chemical composition of aged MATF and MRP derived from laboratory photoaging and actual field sampling were detected, and their effects on cytotoxicity were examined correspondingly. Laboratory photoaging significantly increased environmental persistent free radicals (EPFRs), reactive oxygen species (ROS) abundances and oxidative potential (OP) levels on MATF and MRP, but they have limited cytotoxicity. Unfortunately, in the actual field, aged MATF and MRP with higher heavy metals and polycyclic aromatic hydrocarbons (PAHs) contents exhibited markedly higher cytotoxicity with the survival rate of cells of 78 % and 26 % ( p < 0.05), although they had lower EPFRs and ROS yields. Correlation analysis revealed that the cell viability was closely linked to heavy metals of MATF ( p < 0.05), and to organic hydroperoxide (OHP), PAHs and heavy metals of MRP ( p < 0.05). By systematically considering the above results, heavy metals and PAHs enriched on MATF and MRP from the surrounding environment played the important role in the cytotoxicity, which was different from conventional perspectives. Our findings demonstrate that MATF and MRP associated with an artificial turf field contain potent mixtures of pollutants and can, therefore, be relevant yet underestimated factors contributing to the health risks.